The impact of the use of immunosuppressive treatment after an embryo transfer in increasing the rate of live birth - Andreescu, Mihaela (Frontiers in Medicine, 2023)
The tolerance of the immune system for the semi-allogeneic embryo is promoted by several factors and the cells involved in the immune system and factors in the mother during pregnancy. The dysregulation of the immune responses between the mother and fetus is a risk factor that raises the likelihood of rejection of the embryo and reproductive failure. To safeguard embryos and prevent immunological attacks, it is critical to suppress immunological rejection and encourage immunological tolerance. Based on current medical literature, it seems that immune cell management through immunosuppressive therapies can address reproductive failures. Immunosuppressive treatment has demonstrated encouraging results in terms of enhancing outcomes related to pregnancy and rates of live birth by regulating the immune responses of mothers and positively impacting the reproductive processes of humans. Currently, there is scarcity of high-quality data regarding the safety and efficacy of immunosuppressive therapies for children and mothers. Therefore, it is important to exercise caution while selecting use of any immunosuppressive therapy in pregnancy. This mini review provides a comprehensive overview of the existing literature regarding the impact of Calcineurin Inhibitors and anti-TNF treatment on improving the live birth rate following embryo transfer.